Designing a High Enrollment Asynchronous Core Curriculum Science Course, General Animal Science for Declared Non-animal Science Majors - Frenzel, Leslie (J Anim Sci, 2021)
General Animal Science is a core curriculum science class providing students with an overview of the livestock industry. This case study describes delivery of a high enrollment (n = 634) asynchronous core curriculum science class, General Animal Science, for non-animal science majors. The class progresses from basic agriculture nomenclature, to reproduction, nutrition, genetics, food safety, and concludes with growth and development of beef, sheep, horses, swine, dairy, poultry, and provides a brief description of the companion animal industry. Asynchronous design requires clear and repetitive communication, organized course content, and effective faculty and student engagement. Use of multiple platforms including a learning management system (Canvas), email, and video announcements is helpful for communication and a detailed schedule creates expectations for course progression, vital in an asynchronous course. While content was delivered primarily via lecture and supplementary materials, optional zoom sessions and virtual office hours generate additional engagement opportunities. Learning outcomes were assessed via weekly topic-focused formative student activities and quizzes vs conventional summative exams. Automated grading of assessments provided students with frequent, real-time feedback. In a post-course survey conducted among students enrolled in the Fall 2020 course (n = 634), 97.9% of respondents agreed that course participation was a valuable learning experience and the majority (50.5%) attributed it to lectures, 22% to assignments, 12.2% to group projects, 11.04% to supplementary materials, and 3.9% to optional office hours. Respondents indicated a mean score of 2.02 (SD 2.84) on a Likert scale (0–10) on likely to change their major to Animal Science. This was expected as Biomedical sciences, Agribusiness, Economics, Psychology, and Business were the most frequently declared majors. We concluded that structured schedule utilizing multiple methods of communication and formative assessments are valuable components of a large asynchronous core curriculum general animal science course, and that this course has potential to educate and engage non-animal science majors.